How Things Work - Farndon, John. (Broomall, Pa. : MC Publishers, 2009)
Introduces the technology behind buildings, bridges, transportation, computers, communications, microscopes and telescopes, lasers, X-rays, and entertainment devices.
Machine power -- Construction -- Bridging the gap -- On the rails -- On the road -- On the water -- In the air -- Space walk -- Electronic brains -- Instant contact -- Super vision -- Lasers and X-rays -- Sound and vision -- Mass media.
"First published in 2004 by Miles Kelly Publishing Ltd., Bardfield Centre, Great Bardfield Essex ..."--T.p. verso.
Includes index.
Keywords: Technology -- Juvenile literature; Technology